(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article highlights the principles of establishing tourist and recreational areas in the mountainous regions of Uzbekistan, with a particular focus on Surkhandarya region. It analyzes natural and geographical factors, historical and cultural heritage, infrastructure development, ecological sustainability, local community involvement, and the use of innovative technologies. The study substantiates that the mountainous areas of Surkhandarya region possess significant potential for the development of new directions in tourism.